THE RELATIONSHIP BETWEEN WORK EFFICACY WITHJOB INSECURITY ON PRODUCTION EMPLOYEESPT “X” SEMARANG - Rini Sulistyawati; Harlina Nurtjahjanti; Unika Prihatsanti (Jurnal EMPATI, 2018)
Post ACFTA, ASEAN harmonization program as an effort towards the ASEAN Economic Community (AEC) will be implemented in 2015. Integration will impact on various sectors include traditional herb medicine industry. The inability of the organization to face these conditions can lead to the threat of layoffs and made employees experience job insecurity. Therefore work efficacy to minimize the perceived job insecurity is needed by employees.The purpose of this research is to find out the relationship between work efficacy with job insecurity production employees of PT "X" Semarang. Study uses 56 production employees on PT "X" Semarang as a research subject. Determination of sample using incidental sampling technique. Methods of data collection using job insecurity scale consists of 32 aitem valid (α= 0.900) and Work Efficacy Scale consists of 28 aitem valid (α= 0.931).The results of the analysis with the simple regression analysis method get rxy = -0.644 with p = 0.000 (p <0.05), meaning that the research hypothesis is accepted and that there is a negative and significant correlation between work efficacy and job insecurity. Negative relationship between the two variables means the higher work efficacy, perceiving job insecurity on production employees will be low and vice versa. Work efficacy providing 41.5% effective contribution against job insecurity. These results indicate that there is 58.5% of another factor, which also contributed to job insecurity that are not disclosed in this study.